Vascular complications of renal transplant - Onur, Mehmet Ruhi; Dogra, Vikram (W.B. Saunders, 2013)
Renal transplant provides much longer survival than hemodialysis and peritoneal dialysis for patients with end-stage kidney disease. The prevention of complications in recipients improves survival rates. Imaging studies are crucial for early recognition of vascular complications of renal transplant. Ultrasound is the key imaging method in the evaluation of renal transplants in the immediate postoperative period and the long-term follow-up. Color flow Doppler ultrasound depicts most vascular complications. © 2013 Elsevier Inc.
Keywords: Doppler; Renal transplantation; Ultrasound; Vascular complications